2015
DOI: 10.1056/nejmoa1500858
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Evolocumab in Reducing Lipids and Cardiovascular Events

Abstract: During approximately 1 year of therapy, the use of evolocumab plus standard therapy, as compared with standard therapy alone, significantly reduced LDL cholesterol levels and reduced the incidence of cardiovascular events in a prespecified but exploratory analysis. (Funded by Amgen; OSLER-1 and OSLER-2 ClinicalTrials.gov numbers, NCT01439880 and NCT01854918.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
963
1
42

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,399 publications
(1,037 citation statements)
references
References 26 publications
31
963
1
42
Order By: Relevance
“…Notably, the scenario using a post‐hoc cardiovascular‐event reduction from a randomized open‐label extension study9 of evolocumab found a lower ICER than the base case (which used the CTTC rate ratios3). …”
Section: Discussionmentioning
confidence: 98%
“…Notably, the scenario using a post‐hoc cardiovascular‐event reduction from a randomized open‐label extension study9 of evolocumab found a lower ICER than the base case (which used the CTTC rate ratios3). …”
Section: Discussionmentioning
confidence: 98%
“…Future trials targeting individuals with high Lp(a) using statins (to lower LDL‐C), niacin, proprotein convertase subtilisin kexin type 9 (PCSK9) inhibitors,34, 35 or specific Lp(a)‐lowering antisense therapies36 are clearly warranted to confirm the benefits of lipid‐lowering in individuals with high Lp(a), and should pay special attention to the subgroup with concomitant elevations of LDL‐C, who may be at highest cardiovascular risk. It is noteworthy that PCSK9 inhibitors have shown promising results with respect to significantly lowering both Lp(a) and LDL‐C and may serve as the future preferred treatment strategy for patients with familial hypercholesterolemia with combined elevations of Lp(a) and LDL‐C 34, 35, 37.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that PCSK9 inhibitors have shown promising results with respect to significantly lowering both Lp(a) and LDL‐C and may serve as the future preferred treatment strategy for patients with familial hypercholesterolemia with combined elevations of Lp(a) and LDL‐C 34, 35, 37. Anacetrapib, the only cholesteryl ester transfer protein inhibitor currently under investigation, has also been suggested to effectively reduce both LDL‐C and Lp(a) levels 38.…”
Section: Discussionmentioning
confidence: 99%
“…Alirocumab and evolocumab, either alone or in combination with statins and/or other lipid‐lowering therapies, have been shown in their respective phase 3 clinical trial programs (ODYSSEY and PROFICIO [Program to Reduce LDL‐C and Cardiovascular Outcomes Following Inhibition of PCSK9 In Different Populations]) to significantly reduce LDL‐C levels by up to 60% from baseline (depending on dosing regimen; Table) in patients with hypercholesterolemia, including those with familial hypercholesterolemia, moderate to very high cardiovascular risk, and statin intolerance 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62. The inclusion/exclusion criteria and other details of each phase 3 ODYSSEY and PROFICIO trial are shown in Table S2.…”
Section: Pcsk9 Inhibitors and Their Effects In Patients With Diabetesmentioning
confidence: 99%
“…The cardiovascular benefits of LDL‐C reductions with a PCSK9 inhibitor were first suggested by the post‐hoc analyses of the phase 3 LONG TERM and OSLER trials 58, 62. Recently, the GLAGOV study found that the addition of evolocumab to statin therapy in patients with angiographic coronary artery disease could lead to regression of atherosclerotic plaques after 76 weeks of treatment in those patients with LDL‐C reductions 64.…”
Section: Impact Of Pcsk9 Inhibitors On Atherosclerosis and Cardiovascmentioning
confidence: 99%